Ballett Frankfurt Review from the Festival's Anniversary Season - Orjales-Mourente, Francisco Javier (Dance Books Ltd., Alton,Hampshire (UK), 2003)
Review from the Dance Umbrella Festival's Anniversary Season. PALABRAS CLAVE: Ballett Frankfurt, William Forsythe, Kammer / Kammer.
Dentro del apartado "Silver Jubilee: Dance Umbrella at 25".